High baseline prevalence of atopic comorbidities and medication use in children treated with allergy immunotherapy in the REAl-world effeCtiveness in allergy immunoTherapy (REACT) study - Fritszching, Benedikt; Porsbjerg, Celeste; Buchs, Sarah; Larsen, Julie Rask; Freemantle, Nick; Contoli, Marco (Frontiers in Pediatrics, 2023)
Background: Respiratory allergy, commonly manifesting as allergic rhinitis (AR) and asthma, is a chronic progressive disease that frequently starts in childhood. Allergy immunotherapy (AIT) is the only causal treatment for respiratory allergy with the potential to modify the underlying cause of allergy and, ultimately, prevent disease progression. This analysis aimed to determine if AIT is received sufficiently early to halt the progression of allergic disease, by characterizing the burden and progression of disease in children prior to AIT initiation in real-life clinical practice. Methods: The REAl-world effeCtiveness in allergy immunoTherapy (REACT) study was a large retrospective cohort study using German claims data between 2007 and 2017. Characteristics of two pre-defined AIT age cohorts from the REACT study – children (aged <18 years) and adults (aged ≥18 years) – were evaluated during the 1-year period before the first AIT prescription. For comparison, a control group of all subjects with a confirmed diagnosis of AR and without prescriptions for AIT was included. Burden of disease was assessed using diagnostic codes for atopic comorbidities (e.g., atopic dermatitis [AD], asthma, and acute allergic conjunctivitis) and non-atopic comorbidities (e.g., migraine, headache); medication use, recorded as prescriptions for symptom-relieving AR medication and reliever/controller medication for asthma, was also assessed. Data were analyzed descriptively, using summary statistics. Results: Both children (n=11,036) and adults (n=30,037) showed a higher prevalence of atopic comorbidities and a greater drug burden prior to AIT initiation compared to AR patients not treated with AIT (n=1,003,332). In the two age-specific AIT cohorts, children consistently showed the highest prevalence of atopic comorbidities compared to adults (AIT children, AIT adults: asthma: 41.4%, 34.5%; AD: 19.9%, 10.2%; acute allergic conjunctivitis: 13.6%, 10.2%). Generally, prescriptions per year for symptom-relieving AR and asthma treatments were also higher for children initiating AIT versus adults (AIT children, AIT adults: AR prescriptions per subject: 1.72, 0.73; asthma prescriptions per subject: 1.42, 0.79). Conclusions: Children with AR who are offered AIT in real-life show considerable disease burden prior to initiation. As AIT may alleviate the burden, and halt the progression, of allergic disease, considering AIT earlier in the disease course may be warranted.